2022
DOI: 10.3390/jcm11237238
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection and Outcomes in Children with Inflammatory Bowel Diseases: A Systematic Review

Abstract: The impact of COVID-19 on pediatric patients with inflammatory bowel disease (PIBD) is still not clear and the knowledge acquired over the last 2 years is still evolving. This study aims to investigate the risk and clinical outcomes of COVID-19 in patients with PIBD. A systematic search of PubMed and Scopus databases was conducted to identify studies published up until September 2022. Out of the 475 articles screened, 14 studies were included in the review. Of the 4006 children with PIBD included, 390 (9.7%) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(116 reference statements)
1
2
0
1
Order By: Relevance
“…In a recent systematic review of 4006 children with IBD, 390 (9.7%) tested positive for SARS-CoV-2. Out of the 339 patients in whom the clinical course was reported, only 20 (5.9%) were hospitalized and two (0.6%) required admission to the ICU, with no deaths reported [22]. These findings support previous observations that outcomes in children with IBD and COVID-19 are similar to those in healthy children.…”
Section: Covid-19 In Patients With Inflammatory Bowel Diseasesupporting
confidence: 84%
“…In a recent systematic review of 4006 children with IBD, 390 (9.7%) tested positive for SARS-CoV-2. Out of the 339 patients in whom the clinical course was reported, only 20 (5.9%) were hospitalized and two (0.6%) required admission to the ICU, with no deaths reported [22]. These findings support previous observations that outcomes in children with IBD and COVID-19 are similar to those in healthy children.…”
Section: Covid-19 In Patients With Inflammatory Bowel Diseasesupporting
confidence: 84%
“…The exact reason for the association between certain underlying diseases and COVID-19 severity among older individuals was not clear, which should be explored in the future. Similarly, Batsiou, A. et al reviewed SARS-CoV-2 infection and outcomes in children with inflammatory bowel disease (IBD) and showed that IBD patients with SARS-CoV-2 infection did not have a more severe clinical course or disease progression [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kinder und Jugendliche mit CED haben wie gesunde Kinder ein geringes Risiko für einen schweren Verlauf einer SARS-CoV-2 Infektion im Vergleich zu Erwachsenen. In einem systematischen Review von 14 Studien mit insgesamt 4006 pädiatrischen CED-Patienten wurden von 390 Patienten (9,7 %) mit nachgewiesener Infektion nur 5,9 % hospitalisiert und 0,6 % benötigten eine Behandlung auf eine Intensivstation; Todesfälle traten nicht auf [33].…”
Section: Leitlinieunclassified